Headspace solid-phase microextraction method for extracting volatile constituents from the different parts of Saudi Anethum graveolens L. and their antimicrobial activity. Issue 3 (March 2022) - Aati, Hanan Y.; Perveen, Shagufta; Aati, Sultan; Orfali, Raha; Alqahtani, Jawaher H.; Al-Taweel, Areej M.; Wanner, Juergen; Aati, Abdulrahman Y.
Abstract: Anethum graveolens L. is a famous aromatic herb that is widely used as a spice and has been applied in folk medicine to cure many diseases. The current work was carried out to compare the chemical composition and antimicrobial potency of essential oils obtained from the different parts of Saudi Arabia. graveolens . The oil constituents were extracted by headspace solid-phase microextraction and were quantified and qualitatively identified using GC/MS. As a result, essential oil isolated from A. graveolens seeds exhibited the highest antimicrobial activity compared to oils isolated from other parts, followed by flowers, leaves and stems. All tested A. graveolens essential oil samples exhibited stronger antifungal activities against Aspergillus parasiticus when compared to itraconazole. To the best of our knowledge, the current work is the first report comparing different parts of Saudi A. graveolens plant with respect to their essential oil chemical composition and antimicrobial potentials. The essential oil of A. graveolens seeds have the highest contents of carvone and limonene and show superior antimicrobial activities compared to other parts of the plant. Graphical abstract: Image 1 Highlights: Headspace Solid-phase Microextraction (HS-SPME) is highly effective for analyzing volatile constituents. The essential oil of Dill plays a critical role in its antimicrobial activity. HS-SPME method can be successfully applied for extracting and separating volatile constituents in different parts of A. graveolens plants and more effective for identifying and collecting more constituents. Abstract : A. graveolens ; Dill; Chemical composition; Antimicrobial; Antifungal.